2015
DOI: 10.1007/s12070-015-0886-8
|View full text |Cite
|
Sign up to set email alerts
|

Masson’s Hemangioma of the Cheek: A Case Report

Abstract: We report a rare case of intravascular papillary endothelial hyperplasia (IPEH) of the cheek. This neoplasm, known as Masson's tumor, is an unusual vascular lesion of proliferating endothelial cells. It is usually confined to the lumen of preexisting vessels or vascular malformations. The principal significance of IPEH is its resemblance to a variety of benign and malignant diseases and possible misdiagnosis as such. Achieving a correct diagnosis is essential to avoid subjecting a patient to either unnecessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, its pathogenesis remains uncertain, and it may occur after a traumatic or inflammatory event [ 4 ], through endothelial cell proliferation resulting from a thrombus or secondary to vascular lesions [ 5 ]. With thrombus formation, there is blood stasis, and macrophages can be activated, they stimulates endothelial cell proliferation with papillary formations by releasing fibroblast growth factor contributing to a continuous process that leads to its progression [ 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its pathogenesis remains uncertain, and it may occur after a traumatic or inflammatory event [ 4 ], through endothelial cell proliferation resulting from a thrombus or secondary to vascular lesions [ 5 ]. With thrombus formation, there is blood stasis, and macrophages can be activated, they stimulates endothelial cell proliferation with papillary formations by releasing fibroblast growth factor contributing to a continuous process that leads to its progression [ 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…IPEH comprises 2 to 4% of all vascular tumors of the skin and soft tissues, with the more common occurrences in the extremities (with a predilection for fingers), although they may occur anywhere, with an increasing number of reports demonstrating lesions arising in novel locations. [9][10][11][12] The incidence of IPEH mostly occurs in the third and fourth decades of life, with no gender predilection, although some studies have suggested that it is more common in females, suggesting a hormonal factor in the development of this lesion. 8,13 Recurrence of IPEH is rare and Corni et al reported that a 15% recurrence rate is noted in literature.…”
Section: Discussionmentioning
confidence: 99%
“…One is an intravascular endothelial cell proliferation with papillary formation, which could advance to necrosis and degeneration [5]. Alternative mechanisms include exuberant endothelial proliferation with papillary formation originating from a thrombus; blood stasis and perivascular inflammation; a pseudotumor lesion derived by a cumulative process of thrombotic materials [5,14]. With regard to associations between IPEH and thrombus, it has been proposed that the thrombotic process may have a causative role.…”
Section: Discussionmentioning
confidence: 99%